Новый род и виды клещей семейства Pyemotidae (Тгоmbidiformes) и их положение в семействе - Севастьянов, В.Д. (Вестник зоологии, 1969)
A description is given of new three species of mites from the Pyemotidae family: Pygmephorus chmelnickensis sp. n., Piniphorus drymophilus gen. et sp. n., Pitiiphorus palyctenus gen. et sp. n. The representatives of the genus Piniphorus gen. n. differ from the other genera of the Pyemotidae family in epimerites I which reach epimerons I and form a groove for gnathosoma. Pygmephorus chmelnickensis are close to P. arboris К r c z a 1. 1959 and differ in bulges on setae of Prae, Prai, Poi and in proportions of setae arranged on dorsal and ventral surfaces of the body. The types of these species are preserved in the collection of mites in the Zoological museum of the Institute of Zoology of the Ukrainian Academy of Sciences.